2012
DOI: 10.1017/s1462399411002109
|View full text |Cite
|
Sign up to set email alerts
|

PI3K/AKT, MAPK and AMPK signalling: protein kinases in glucose homeostasis

Abstract: New therapeutic approaches to counter the increasing prevalence of obesity and type 2 diabetes mellitus are in high demand. Deregulation of the phosphoinositide-3-kinase (PI3K)/v-akt murine thymoma viral oncogene homologue (AKT), mitogen-activated protein kinase (MAPK) and AMP-activated protein kinase (AMPK) pathways, which are essential for glucose homeostasis, often results in obesity and diabetes. Thus, these pathways should be attractive therapeutic targets. However, with the exception of metformin, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
300
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 391 publications
(327 citation statements)
references
References 167 publications
(194 reference statements)
8
300
0
2
Order By: Relevance
“…Besides the effects on the liver and skeletal muscle, studies have shown that metformin activates AMPK in aortic endothelial tissue in vivo (Zou et al 2004). Therefore, it can be stated that some of the mechanisms of action of metformin may be explained by AMPK activation (Schultze et al 2012, Viollet et al 2012.…”
Section: Glucose Uptake Pathwaysmentioning
confidence: 99%
“…Besides the effects on the liver and skeletal muscle, studies have shown that metformin activates AMPK in aortic endothelial tissue in vivo (Zou et al 2004). Therefore, it can be stated that some of the mechanisms of action of metformin may be explained by AMPK activation (Schultze et al 2012, Viollet et al 2012.…”
Section: Glucose Uptake Pathwaysmentioning
confidence: 99%
“…Activation of the phosphatidylinositol 3-kinase (PI3K)-AKT/PKB pathway is considered the main signaling component downstream of the insulin receptor (3,4). When activated, AKT regulates a multitude of targets by direct phosphorylation (5).…”
mentioning
confidence: 99%
“…The PI3K/AKT pathway also plays an evolutionarily conserved role in glucose metabolism where it acts to transduce intracellular signals downstream of insulin and the insulinlike-growth factor (3). The 3 AKT isoforms (AKT1, 2, and 3) are highly homologous yet differ in quantitative levels of tissuespecific expression, which determines the relative contribution of each isoform to glucose metabolism and insulin signaling (4)(5)(6).…”
mentioning
confidence: 99%